P11.09.B Chemotherapy is an efficient treatment in primary CNS MALT lymphoma. (5th September 2022) - Desjardins, C; Larrieu-Ciron, D; Choquet, S; Mokhtari, K; Charlotte, F; Nichelli, L; Mathon, B; Ahle, G; Le Garff-Tavernier, M; Dehais, C; Hoang-Xuan, K; Houillier, C
Abstract: Background: Mucosae-associated lymphoid tissue (MALT) lymphomas are a rare and still poorly understood form of primary central nervous system lymphoma (PCNSL). The aim of this study was to better describe these tumors and their management, and to better appreciate their long-term prognosis after treatment. Material and Methods: Adult immunocompetent patients with primary CNS MALT lymphoma (PCNSML) were retrospectively selected from the database on PCNSL of the Pitié-Salpêtrière Hospital. All cases had double-read for pathology. Results: Eleven PCNSML representing 1.7% of the 662 PCNSL included in the database were selected, There were 9 women and two men, all immunocompetent. Their median age was 56 years (min 29; max 78). The median time from first symptoms to diagnosis was 13 months and the median KPS at diagnosis was 90. Location was dural in 8 cases, suggestive of meningioma in 7 cases and of subdural hematoma in 1 case, and parenchymal in 3 cases. The disease was unifocal/localized in 4 cases and multifocal/diffuse in 7 cases. In 3 cases, it was the second reading that allowed making the diagnosis. In first-line treatment, all patients received chemotherapy (CT): "systemic" CT, i.e usually used in systemic MALT lymphomas, in 7 cases (n=7) and "CNS" CT, i.e usually used in CNS lesions in 4 cases. CT was preceded by surgery in 4 cases. No patient received radiotherapy in first line. According to the IPCG (International PCNSL Collaborative Group) criteria, the overall response rate was 7/11 (64%). At latest news, 5 patients had a persistent contrast enhancement, stable without any treatment since a median of 57 months, raising the question of complete response despite persisting contrast enhancement. No patient developed neurotoxicity except for one of the 2 patients who subsequently received radiotherapy. The median follow-up was 109 months. The median progression-free survival was 78.0 months (95% CI [43.4;NA[) and the 10-year overall survival rate was 90% (95% CI [0.7;1[). Conclusion: This series confirms the classical clinical and radiological presentation of PCNSML. Compared to the literature where the treatment was based on radiotherapy in almost two thirds of cases, the therapeutic approach presented here appears unconventional. This is the first series demonstrating that chemotherapy is an efficient treatment in PCNSML, with an excellent long-term outcome and the absence of neurotoxicity, and calling into question the relevance of the IPCG criteria for the evaluation of their therapeutic response.